HORIZONTAL WELL PERFORMANCE MODELLING USING PSEUDOWELL TECHNIQUE - Tunggal Tunggal (Scientific Contributions Oil and Gas, 2000)
The potential improvement of horizontal productivity has been recognized since mid 1950s, where horizontal well allows longer flow interval hence higher flow rate with lower pressure drawdown. Such remarkable productivity improvement has fascinated the great interest of petroleum industries around the world to fit the role of effective field development strategy. The objective is to reduce the overall cost of field development. In the case of offihore oil fields, the horizontal well drilling is desired to eliminate required number of vertical wells and utilizing of expensive sub-sea technology. The continuous development and application of horizontal well drilling technologies have been reported in many publications, Nowadays, the horizontal well drilling and completion with complex trajectory is possible. However, the costs required by horizontal well drilling and completion is still considerably more expensive than the vertical one. The future needs of horizontal well drilling tend to arise depending on the economical aspect by means the horizontal well productivity outweigh the incremental drilling and completion costs. An adequate method is required to estimate it's expected productivity to determine the economic feasibility. This paper proposes a horizontal well performance modeling by the concept of pseudowell technique.